2019
DOI: 10.1080/15592324.2019.1613131
|View full text |Cite
|
Sign up to set email alerts
|

Research advances of MYB transcription factors in plant stress resistance and breeding

Abstract: Plants face various stresses during the growth and development processes. The specific transcription factors bind to the cis-acting elements upstream of the stress resistance genes, specifically regulating the expression of the gene in plants and increasing the adaptability of plants to environmental stress. The transcription factor-mediated gene expression regulatory networks play an important role in plant stress response pathways. MYB (v-myb avian myeloblastosis viral oncogene homolog) transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 119 publications
1
112
0
1
Order By: Relevance
“…Plant △ ∼ 1-pyrroline-5-carboxylic acid synthase ( P5CS ) is a key enzyme involved in proline synthesis, and it is also important for abiotic stress responses ( Li et al, 2018 ; Arabbeigi, Arzani & Majidi, 2019 ). Ascorbate peroxidase ( APX ) plays an important role in plant abiotic stress, and is an important index for measuring stress responsiveness ( Li et al., 2019a ; Li et al., 2019b ; Cunha et al, 2019 ). Our experimental results indicated that the overexpression of SlMYB102 can increase both APX2 and P5CS expression ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant △ ∼ 1-pyrroline-5-carboxylic acid synthase ( P5CS ) is a key enzyme involved in proline synthesis, and it is also important for abiotic stress responses ( Li et al, 2018 ; Arabbeigi, Arzani & Majidi, 2019 ). Ascorbate peroxidase ( APX ) plays an important role in plant abiotic stress, and is an important index for measuring stress responsiveness ( Li et al., 2019a ; Li et al., 2019b ; Cunha et al, 2019 ). Our experimental results indicated that the overexpression of SlMYB102 can increase both APX2 and P5CS expression ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…MdMYB88 and MdMYB124 actively regulate frost tolerance and cold response gene expression in apples and in A. thaliana (Xie et al, 2018), while PbrMYB5 controls AsA synthesis by regulating the expression of dehydroascorbate reductase (DHAR2), thereby improving the cold resistance of transgenic tobacco plants (Xing et al, 2019). These past studies provide clear evidence for the vital role of plant MYB family transcription factors in abiotic stress responses (Abe et al, 1997;Li et al, 2019a;Li et al, 2019b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Myb is another TF that is well characterized as a Ca 2+ /CaM-dependent protein. It acts upstream to a number of defense-responsive, salinity, and drought-receptive genes ( Do Heo et al, 1999 ; Stracke et al, 2001 ; Li et al, 2019 ). CaM also supports transcriptional repression interceded by CBNAC/NTL9 ( Kim et al, 2007 ).…”
Section: Calcium: a Second Messenger And Its Interaction With Calmodumentioning
confidence: 99%
“…The GRAS and MYB TF families are two of the most over-represented families in cycling transcripts that are downregulated in response to heat, especially during the early response (Table S1). These two families participate in many aspects of plant growth and development [94,95]. Thus, transcriptional regulation of these family members under heat reflects the adjustment of developmental processes in response to this stress.…”
Section: Time Of Day and Other Clock-regulated Heat Responsive Transcmentioning
confidence: 99%